Right of participation in business as matrimonial property: the Malaysian experience - Abd Ghadas, Zuhairah Ariff; Ibrahim, Norliah (International Islamic University Malaysia, 2007)
It is a deep wish of 'most' married couples that the marriage will last until 'death do as part.' Nonetheless, despite this wish, it is often found that a crisis occurs between married couples when it comes to money matters, more so if the concern is about a business which both parties foresee as a source of wealth. The right of paticiation in business is more than the right to share profits of the business. It also involves the management right and decision making power. Upon a divorce, it is common for the lucky ex-spouse to get certain percentage of shares in the business and therefore entitled to certain amount of dividend anually but rarely does one find the right to participation in the business is retained or given to the ex-couples. Whilst in practice the right to participate in the business is more significant and worth more than shares! This article looks into participation rights in business as part of the matrimonial property in the due course of a divorce.